Depot- and sex-specific effects of maternal obesity in offspring's adipose tissue. Issue 1 (July 2016) - Lecoutre, Simon; Deracinois, Barbara; Laborie, Christine; Eberlé, Delphine; Guinez, Céline; Panchenko, Polina E; Lesage, Jean; Vieau, Didier; Junien, Claudine; Gabory, Anne; Breton, Christophe
Abstract : According to the Developmental Origin of Health and Disease (DOHaD) concept, alterations of nutrient supply in the fetus or neonate result in long-term programming of individual body weight (BW) setpoint. In particular, maternal obesity, excessive nutrition, and accelerated growth in neonates have been shown to sensitize offspring to obesity. The white adipose tissue may represent a prime target of metabolic programming induced by maternal obesity. In order to unravel the underlying mechanisms, we have developed a rat model of maternal obesity using a high-fat (HF) diet (containing 60% lipids) before and during gestation and lactation. At birth, newborns from obese dams (called HF) were normotrophs. However, HF neonates exhibited a rapid weight gain during lactation, a key period of adipose tissue development in rodents. In males, increased BW at weaning (+30%) persists until 3months of age. Nine-month-old HF male offspring was normoglycemic but showed mild glucose intolerance, hyperinsulinemia, and hypercorticosteronemia. Despite no difference in BW and energy intake, HF adult male offspring was predisposed to fat accumulation showing increased visceral (gonadal and perirenal) depots weights and hyperleptinemia. However, only perirenal adipose tissue depot exhibited marked adipocyte hypertrophy and hyperplasia with elevated lipogenic (i.e. sterol-regulated element binding protein 1 ( Srebp1 ), fatty acid synthase ( Fas ), and leptin) and diminished adipogenic (i.e. peroxisome proliferator-activated receptor gamma ( Pparγ ), 11β-hydroxysteroid dehydrogenase type 1 ( 11β-Hds1 )) mRNA levels. By contrast, very few metabolic variations were observed in HF female offspring. Thus, maternal obesity and accelerated growth during lactation program offspring for higher adiposity via transcriptional alterations of visceral adipose tissue in a depot- and sex-specific manner.